2021
DOI: 10.33225/pec/21.79.255
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate Supervision Practices in Education Research and the Creation of Opportunities for Knowledge Sharing

Abstract: Supervisory practices are fundamental to the production of research in higher education, but these practices are undertheorized and poorly understood. Academia needs to understand and engage with supervisory pedagogies to reinforce their importance in knowledge production and the development of a knowledge society. Using content analysis of master’s and doctoral research outputs completed between 2010 and 2016, this case study investigated postgraduate supervision practices in education in South Africa, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…To make supervision more effective, supervisors can apply some basic supervision models to suit different groups of students, thereby improving the quality of supervision. According to Ngulube (2021), supervision and supervision models are notoriously vague, and there is no standard nomenclature for the description of Supervision Models. However, another study by Lee (2012) prefers supervisory models as approaches and proposes five vital conceptual styles: functional (directed), enculturation (contractual), critical thinking, emancipation (lasses-faire), and relationship development (pastoral).…”
Section: Supervision Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…To make supervision more effective, supervisors can apply some basic supervision models to suit different groups of students, thereby improving the quality of supervision. According to Ngulube (2021), supervision and supervision models are notoriously vague, and there is no standard nomenclature for the description of Supervision Models. However, another study by Lee (2012) prefers supervisory models as approaches and proposes five vital conceptual styles: functional (directed), enculturation (contractual), critical thinking, emancipation (lasses-faire), and relationship development (pastoral).…”
Section: Supervision Modelmentioning
confidence: 99%
“…Alternatively, in the "Therapeutic" supervision model, Currie (2019) suggested that the monitoring model can help strengthen the relationship between their supervision and student or address the counseling relationship between their supervisees and supervisees' clients over the concrete professional development issues in supervision. A study by Ngulube (2021) launched a one-to-one monitoring model, also known as "the traditional apprentice-master model." This model is one in which the person conducting the research project will study them alone under single supervision.…”
Section: Supervision Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently an ongoing debate regarding supervision models, approaches, and styles. Ngulube, (2021) outlined that Phillips and Pugh (1994) make no distinction between supervision styles and approaches, but Lee (2012) considers supervision models as approaches. Whilst for Mouton (2001), styles or approaches are interchangeable and can determine the roles that the supervisor assumes in relation to the supervisee.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above mentioned knowledge produced on postgraduate supervision, the completion of master and doctoral studies is of great concern regarding time spent to graduation and the limited project resources and relation to the project timeline. There is need to assess supervisory practices which are undertheorised and poorly understood (Ngulube, 2021) and to provide further research on how completion rate from four to seven years (4-6 years more in Ghana (Akparep, Jengre, & Amoah, 2017), 6.19 years in Ethiopia (Fetene & Tamrat, 2021) can be improved. In the case of poor or unclear recorded procedures to guide postgraduate supervision, supervisors tend to develop their own rules and styles.…”
Section: Introductionmentioning
confidence: 99%